Spatio-temporal variability of droughts over the Mullaitivu District in Sri Lanka from 1980 to 2020 - Piratheeparajah Nagamuthu,; Tan, Mou Leong; Chan, Ngai Weng; Zhang, Fei (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research aims to evaluate the spatio-temporal changes of annual and seasonal droughts of the Mullaitivu District in Sri Lanka from 1980 to 2020 using the Standardized Precipitation Index (SPI). Four homogeneity tests were performed to identify the inhomogeneity of the monthly rainfall data obtained from twelve stations. Good quality observed data were chosen to measure SPI for determining the frequency, severity, and intensity of the drought events. This was followed by Mann Kendall's (M-K) test to analyze the drought occurrences trend. Further, the relationship between the drought events and Indian Ocean Dipole (IOD) was explored to understand how large-scale atmospheric circulation influences the local droughts. The findings show that dry periods occurred in 1982, 1998, and 2018, while 1989, 1992, 1994, 2001, 2003, 2007, and 2011 experienced severe dry phases. In addition, June, July, and August were identified as the dry months in the study area. Spatially drought over the Mullaitivu District spread from west to east, where the drought vulnerability originated in the west in March and moved eastward. A strong positive correlation (r = 0.83) between the drought events and IOD showed that IOD has considerably influenced the drought formation over the Mullaitivu District.